How Do the Exchange Rates Affect the Sector Indices? A Dynamic Panel Data Analysis for Borsa Istanbul - Hande Aksöz Yılmaz; Fatih Güzel (İstanbul İktisat Dergisi)
This paper aims to investigate the impact of the exchange rate on stock market indices of four main sectors in Turkey. For this purpose, the paper uses monthly data spanning the period between 06/2008-11/2020 and employs the panel GMM estimation method. This method instrumentalizes the past observation values of the dependent variable to control the endogeneity and provides efficient results. Considering that firms operating in many sectors in Turkey are affected by the volatility of the exchange rate, the paper takes initiative in understanding how stock market indices of four sectors react to the fluctuation in USD and Euro prices. This study contributes to the current literature, performing the panel GMM estimation method, unlike studies that only examine the causality relationship on the link between exchange rate and the stock market. The results show that there is unidirectional causality from the exchange rate to stock market indices. According to our findings, the USD/TRY exchange rate negatively affects stock market indices, and the Euro/TRY exchange rate positively affects stock market indices. The findings obtained from the analysis results confirm prior knowledge acquired from Turkey’s foreign trade structure.